Burnout and Empathic Tendency Levels in Emergency Nurses - Tuğba Çınarlı; Zeliha Koç; Latif Duran (Eurasian Journal of Emergency Medicine, 2016)

(untitled)
Aim: It is important to determine the factors affecting burnout and empathic tendency levels among emergency nurses in order to increase satisfaction with healthcare service in patients and their relatives and to increase the quality of healthcare services. The purpose of the present study was to determine the factors that affect burnout and empathic tendency levels among emergency nurses.Material and Methods: This was a descriptive and cross-sectional study. Data were collected using the Nurse Identification Form, the Maslach Burnout Inventory (MBI), and the Empathic Tendency Scale (ETS).Results: A total of 129 emergency nurses participated in the study. Among the nurses, 22.5% were males. The mean MBI score of nurses who partially willingly chose the profession, did not like their job, and had poor or very poor quality of work life was found to be higher. The mean ETS score of nurses who willingly or partially willingly chose the profession and who liked their job was higher.Conclusion: Because empathic skills and tendency can be improved with education, the empathic tendency skills of nurses should be improved through continuous education programs.